The Impact of Cardiopulmonary Resuscitation Video Learning Media on Skills Improvement in Nursing Students: Literature Review - Halimatus Sa’diyah; Novita Ana Anggraini; Dedi Saifullah (PT. Griya Eka Sejahtera, 2020)
Background: Understanding and skills of CPR are very important to be applied correctly and correctly, especially the understanding and skills that must be possessed by all health workers, including nurses. At this time, one of the skills that must be possessed by nursing students before becoming a professional nurse is cardiopulmonary resuscitation (CPR). To achieve this ability, appropriate learning methods are needed, one of which is using the audiovisual method. Method: The search for relevant articles or journals is carried out using a database through Google Scholar, Google Scholar, and Pubmed Central (PMC) in the period 2010-2020. The results of the search found 15 articles using nursing interventions but only 12 articles that met the inclusion criteria, namely according to the keywords. The analysis of these 12 journals was carried out based on the design, population, sample, sampling, parameters and conclusions sections. Results From the literature study that has been carried out on research or writing on the same topic, it can be seen that the Cardiopulmonary Resuscitation (CPR) video learning media greatly influences the improvement of skills in nursing students. recall, it will tend to disappear over time. Conclusion: With this, learning media using video can remind what they have learned and can be played over and over again so that they are able to improve the skills of these nursing students